Description of nymphs and ontogenetic morphometry of Triatoma ryckmani Zeledón & Ponce, 1972 (Hemiptera: Heteroptera: Reduviidae: Triatominae) - Rocha, Dayse da Silva; Dale, Carolina; da Rosa, João Aristeu; Galvão, Cleber (EntomoBrasilis, 2020)
Triatoma ryckmani Zeledón & Ponce, 1972 is a species found in sylvatic habitat at Central America. Considered rare in the past and poorly studied, nowadays can be found inside houses with potential of dispersal and colonization. All five instars of T. ryckmani are described based on optical and scanning electron microscopy. The postembryonic development of the head analyzed by ontogenetic morphometry showed the largest changes occur in the first three instars. Information about morphology of the immature stages of disease vectors can be helpful in the identification process increasing speed and efficiency of control strategies.